Cervical lymphatic malformation demonstrating thyroglobulin on fine needle aspirate washout. Issue 12 (7th September 2020) - Agnihotri, Ashwin; Lilic, Nick; Chaplin, John; Braadvedt, Geoffrey; Bagg, Warwick
Abstract: A case report highlighting the importance of cautious interpretation of thyroglobulin washouts in fine needle aspirates when deciding on management of differentiated thyroid cancer, so as to avoid unnecessary surgery. Abstract : A case report highlighting the importance of cautious interpretation of thyroglobulin washouts in fine needle aspirates when deciding on management of differentiated thyroid cancer, so as to avoid unnecessary surgery.